An Evolutionary Perspective on Risk Taking in Tourism. (November 2019) - Kim, Jungkeun; Seo, Yuri
Informed by recent developments in the field of evolutionary psychology, we elicit novel insights about the causal relationship between the activation of mating motives and gender-specific preferences for risk taking in tourism. In this endeavor, across four experimental studies, we illustrate that the effect of activating mating motives on the propensity for risk-taking tourism will be greater for men than it is for women. That is, when mating motives were salient, men consistently displayed a greater preference for the choice of high-risk travel activities (studies 1A and 1B), adventurous destination choices (study 2), and adventurous appeals in travel advertising (study 3). Our findings offer important theoretical contributions to research into the role of gender in risk-taking tourism behaviors from the perspectives both of evolution-based theorizing and managerial implications for tourism practice.